2018
DOI: 10.1002/jsfa.9328
|View full text |Cite
|
Sign up to set email alerts
|

Molecular species determination of oligosaccharides and glycoconjugates in soybean lecithin powders

Abstract: The determination of molecular species of oligosaccharides and glycoconjugates provided a new direction for the exploration of novel functions and uses of soybean lecithin powder. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…GC–MS was applied to determine the fatty acid composition of the mushroom oil and the procedures were performed according to Kang et al. ( 2019 ) with some modifications. In brief, a 20 mg oil sample and 3 mL sodium methoxide solution (0.5 M) were mixed together to enable saponification for 30 min at 70°C, and then, 1 mL boron trifluoride diethyl ether solution was added into the mixture for water bath heating at 80°C for 30 min, which enhanced the production of the fatty acid methyl ester.…”
Section: Methodsmentioning
confidence: 99%
“…GC–MS was applied to determine the fatty acid composition of the mushroom oil and the procedures were performed according to Kang et al. ( 2019 ) with some modifications. In brief, a 20 mg oil sample and 3 mL sodium methoxide solution (0.5 M) were mixed together to enable saponification for 30 min at 70°C, and then, 1 mL boron trifluoride diethyl ether solution was added into the mixture for water bath heating at 80°C for 30 min, which enhanced the production of the fatty acid methyl ester.…”
Section: Methodsmentioning
confidence: 99%
“…Hamaguchi et al 11,12) and Hayashi et al 13,14) reported that PE and sugar in SL react to form four pyridinium derivatives with browning and increased UV absorption at 350 nm, implying that this heat deterioration of SL is unavoidable because SL contains both oligosaccharides 15,16) and PE itself, and heating is essential during cooking.…”
Section: Heating Dspe With Calcium Stearatementioning
confidence: 99%
“…Phytosterol glycosides (PGs) mainly containing acyl‐sterylglucosides (ASGs) and sterylglucosides (SGs), were reported to exist in soybean lecithin powder at ranges of 5% to 10%, but these PG abundant existence was in conflict with phospholipid function, as they showed different effects on vascular integrity, for example, PGs can act as a neurotoxin, a prostaglandin synthetase inhibitor and hemostatic agent by reducing vascular permeability, while lecithins enhanced ability, promotes prostaglandin synthesis, and improves cardiovascular disease via increasing vascular permeability . In addition to the earlier mentioned, PG in soybean lecithin powder can also alter phospholipid phase transition, induce infusion reaction and increase liposome fluidity, making it crucial to remove PG from soybean lecithin powder for high‐quality phospholipid.…”
Section: Introductionmentioning
confidence: 99%
“…As more and more adsorbents were used for adsorbing non‐ionic surfactants or SG removal from biodiesel, the question arises is there an adsorbent that could specifically adsorb PG from lecithin material? Studies on PG enrichment from lecithin material by silica‐gel adsorption aroused our team's attention. Based on principles of maximum comprehensive utilization of soybean lecithin resources, we discussed the feasibility of silica‐gel adsorption to maximize PG extraction at the lowest loss of phospholipids, so phospholipids recovery was also needed to be examined in addition to PG extraction efficiency (ASG and SG).…”
Section: Introductionmentioning
confidence: 99%